Continuous renal replacement therapy: what have we learned and what are key milestones for the years to come? - Pablo Galindo; Javier A. Neyra (Revista de Investigación Clínica, 2023)
Continuous renal replacement therapy (CRRT) is the main extracorporeal kidney support therapy used in critical ill patients in the intensive care unit (ICU). Since its conceptualization ~50 years ago, there have been major improvements in its technology and utilization. The last decade, and particularly since the COVID-19 pandemic, has been marked by a growing interest and demand of CRRT in worldwide ICUs. This has underpinned the need for improvements in nomenclature and process standardization, optimization of CRRT deliverables, and the development and validation of key performance indicators. Further, how to leverage digital health technologies to build clinical decision support for CRRT and improve personalized bedside decisions is a subject of intense investigation. Herein, we summarize notable advancements in the provision of CRRT and propose areas in need of further development.